Fertility and obstetrical outcomes after robot‐assisted laparoscopic myomectomy. Issue 1 (18th December 2019) - Huberlant, Stéphanie; Lenot, Juliette; Neron, Mathias; Ranisavljevic, Noémie; Letouzey, Vincent; De Tayrac, Renaud; Masia, Florent; Warembourg, Sophie
Abstract: Objective: To evaluate fertility after robot‐assisted laparoscopic myomectomy (RALM) in terms of pregnancy rates, and obstetrical outcomes. Patients: This is a retrospective cohort of RALM performed for symptomatic leiomyomas among women who want to conceive. Medical data were retrospectively reviewed. An office hysteroscopy was prescribed 3 months after the surgery. Results: Fifty‐three patients were included. The mean number of myomas was 2 ± 1.5 with a mean size of 69 ± 17.7 mm. A breach of the cavity was noticed in 15.1% of the cases. Two cases of intrauterine adhesions were diagnosed and treated during the post‐operative office hysteroscopy (5.7%). Clinical pregnancy rates were 52.8% with a live birth rate of 41.5% in patients desiring pregnancy. A caesarean section was performed in 17 cases (70.8%). No case of uterine rupture was reported. Conclusion: More than half of the patients became pregnant after RALM. A low rate of obstetrical complications was reported, with no uterine ruptures, highlighting the promise of this technique for infertile patients.